Pengaruh Budaya Organisasi, Komunikasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Gajahmada Nusantarajaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
In an increasingly competitive workplace, employee performance is one of the important factors determining a company’s success. PT Gadjahmada Nusantarajaya, a company engaged in the service and trade sector, faces the challenge of maintaining and improving its employees’ performance. Internal factors such as organizational culture, work communication, and work discipline are thought to have a significant influence on employee performance. Based on this, this study was conducted to determine the influence of organizational culture, work communication, and work discipline on employee performance at PT Gadjahmada Nusantarajaya. The research questions in this study are: (1) Does organizational culture influence employee performance? (2) Does work communication influence employee performance? (3) Does work discipline influence employee performance? and (4) Do organizational culture, work communication, and work discipline simultaneously influence employee performance at PT Gadjahmada Nusantarajaya? This research is quantitative. Data were obtained through primary data collected using a questionnaire, as well as secondary data from company documents. The study population was all 49 employees of PT Gadjahmada Nusantarajaya. The sampling technique used saturated sampling; thus, the entire population was used as the research sample. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests (t-tests and F-tests). The results showed that partially (t-tests) the variables of organizational culture, work communication, and work discipline had a significant effect on employee performance. Simultaneously (F-tests), these three variables also had a significant effect on employee performance at PT Gadjahmada Nusantarajaya.